2016
DOI: 10.1002/acp.3289
|View full text |Cite
|
Sign up to set email alerts
|

Thinking About What Might Have Happened: Counterfactual Thinking and Post‐traumatic Stress in Individuals Directly and Indirectly Exposed to the 2011 Oslo Bombing

Abstract: Counterfactual thinking (CFT), that is thinking about what might have happened, is linked to post-traumatic stress. We studied the relationship between type and frequency of CFT and post-traumatic stress in a sample of directly (n=50) and indirectly exposed (n=50) ministerial employees 4years after the 2011 Oslo bombing. The results showed that frequency of CFT was associated with levels of post-traumatic stress, among both directly and indirectly exposed participants. In the directly exposed group, self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…However, no data on the relationship between direction of CFT and number of PTSD symptoms. In contrast, Blix et al (2016) found a predominance of downward CFT in a study with survivors of a terror attack. In their study, 90% of both directly and indirectly exposed individuals reported a downward counterfactual first whilst the remaining 10% reported an upward counterfactual first.…”
Section: Results Of Individual Studies On Counterfactual Comparative mentioning
confidence: 81%
See 4 more Smart Citations
“…However, no data on the relationship between direction of CFT and number of PTSD symptoms. In contrast, Blix et al (2016) found a predominance of downward CFT in a study with survivors of a terror attack. In their study, 90% of both directly and indirectly exposed individuals reported a downward counterfactual first whilst the remaining 10% reported an upward counterfactual first.…”
Section: Results Of Individual Studies On Counterfactual Comparative mentioning
confidence: 81%
“…Several studies assessed the direction of the first or most predominant CFT that came to mind using a thought listing task (Bhushan & Kumar, 2012;Blix et al, 2016;Dalgleish, 2004). In a study with 20 tsunami relief volunteers, 60% of respondents reported upward CFT first whereas the remaining 40% reported downward CFT first (Bhushan & Kumar, 2012).…”
Section: Results Of Individual Studies On Counterfactual Comparative mentioning
confidence: 99%
See 3 more Smart Citations